Peningkatan Interaksi Ibu dan Anak Retardasi Mental melalui Pelatihan Bermain Pura-Pura - Fithriya, Suci; Lestari, Sri (Jurnal Psikologi, 2014)
This study aimed to prove the influence of training of playing pretense game in increasing mother’s interaction with her mentally-retarded child. There were eight mothers who have under-five-year children with mental retardation participating in the research. They were randomly chosen. The research design used pre-test and post-test control group. Four mothers belonged to the control group and the other four to the treatment group. The training of playing pretense game with children was conducted in four stages. The first and second stages were done in group while the third and fourth were individual. Mother and child interaction scale was used to measure the differences of the interaction before and after the training. The follow-up research was done thirteen days after the training. The results showed the pretense game played by a mother and her mentally-retarded child can make their interaction become more meaningful. Keywords: mother and mentally-retarded child interaction, pretense game training